Analisis Kualitas Informasi Pelaporan Keuangan pada Satuan Kerja Kantor Wilayah Kementerian Agama Provinsi Aceh - Fahriani Fahriani; Darwanis Darwanis (Jurnal Telaah dan Riset Akuntansi, 2016)
Demands for greater public accountability for the implementation implications for public sector management to provide information to the public, one of which is the accounting information in the form of financial statements. Criteria and elements forming the information that makes the quality of information in the financial statements of the government must be known at each business unit. This study aimed to analyze the quality of financial reporting information at the working unit of the Regional Office of Religious Affairs of Aceh province. The population in this study is the entire work unit office in the Ministry of Religion of Aceh totaling 103 work units. The results showed the presence of the competence of human resources and the implementation of internal controls and the implementation of accrual accounting is applied properly will make the quality of financial reporting information at the working unit at the Regional Office of the Ministry of Religion of Aceh increasingly meet the standards.KEYWORDS : human resource competencies, internal controls, accrualbased accounting and the quality of financial reporting information